Research of The Relationship Between Revenues of The World Transnational Companies And Gdp of Individual Countries - Liudmyla NIEMETS1; Pavlo KOBYLIN1; Liudmyla KLIUCHKO1; Kostiantyn NIEMETS1; Yurii KANDYBA1; Gennadii GOLUB2 (Communications of International Proceedings, 2021)
The paper deals with researching the relationship between revenues of the world transnational companies and the GDP of the individual countries. Transnational corporations are a very important agents of globalization processes in the world, their activities are carried out around the world, and they organize global production chains, which involve different countries. These companies are so powerful that the incomes of some of them exceed the GDP of some countries. In this regard, this article aims to establish a relationship between revenues of TNCs and GDP of the countries. The authors used the method of correlation analysis in the article in order to establish these connections. The analysis uses indicators: number of TNCs based in a given country, total income of these companies per country, country's GDP, and GDP per capita. The authors determined the main countries where transnational corporations are based, number of TNCs in the countries, identified correlation coefficients between the parameters. It allowed to establish a direct relationship between the TNCs revenues, the number of transnational corporations and the country's GDP, and lack of relationship between these indicators and GDP per capita. The number of countries whose GDP exceeds TNCs incomes and the ratio of Ukraine's GDP to the Walmart's income is determined.
Keywords: GDP of the country; GDP per capita; TNCs; correlation analysis; communication strength; Fortune global 500; headquarters.